High-entropy metal organic framework compound, high-entropy alloy composite material and preparation method and application of high-entropy metal organic framework compound

By preparing high-entropy metal organic framework compounds and converting them into high-entropy alloy composites, the problem of irreconcilable metal components is solved, flexible control of catalytic activity and metal content is achieved, and catalytic performance is improved.

CN120399254APending Publication Date: 2025-08-01LANZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510531944.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

In the prior art, the metal components in the high-entropy alloy synthesis system are unadjustable, resulting in uncontrollable metal loading and affecting the catalytic effect.

Method used

High-entropy metal organic framework compounds (HEMOFs) were weaved and synthesized by metal ligand strategy. Controllable high-entropy alloy composite materials were prepared by reacting organic ligands with monometal complexes and cerium sources, and high-entropy alloy composite materials were obtained through carbonization and reduction.

Benefits of technology

It realizes flexible control of metal composition and proportion in high-entropy alloy composite materials, improves catalytic performance, and especially shows excellent catalytic activity in photocatalytic hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005376879620000011
    Figure HDA0005376879620000011
  • Figure HDA0005376879620000021
    Figure HDA0005376879620000021
  • Figure HDA0005376879620000022
    Figure HDA0005376879620000022
Patent Text Reader

Abstract

The invention discloses a high-entropy metal organic framework compound, a high-entropy alloy composite material and a preparation method and application of the high-entropy metal organic framework compound and the high-entropy alloy composite material. The high-entropy metal organic framework compound comprises a reaction product of an organic ligand, a monometal complex and a cerium source, the organic ligand comprises 2, 2 '-bipyridine-5, 5'-dicarboxylic acid, and the monometal complex comprises at least five of a Pt complex, a Pd complex, a Ni complex, a Cu complex, an Ag complex, an Rh complex and an Ir complex. The high-entropy alloy composite material prepared from the high-entropy metal organic framework compound as a precursor through carbonization and reduction has adjustable metal content and excellent catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of materials, and particularly relates to a high-entropy metal-organic framework compound and a preparation method thereof, and also relates to a high-entropy alloy composite material prepared from the high-entropy metal-organic framework compound and its application. Background Art

[0002] Multi-metal center catalytic materials can provide multiple adsorption sites (or reaction sites) on their surfaces. The excellent performance of the materials is not only reflected in the simple superposition of each metal element, but more importantly in the synergistic effect between metal elements. Therefore, multi-metal center materials have been widely used in the catalytic field. Among them, alloy catalysts exhibit excellent catalytic performance through the synergistic effect between different metal elements.

[0003] At present, alloy catalysts have been developed to high-entropy alloys (HEAs) with five or more metal elements. High-entropy alloy materials have high-entropy effect, sluggish diffusion effect, lattice distortion effect and cocktail effect. The cocktail effect means that each metal element can not only fully exert its own properties, but also form an alloy with synergistic catalytic effect with other metal elements. Due to the interaction between different metal elements, the d-band center of the alloy will change, showing a controllable adsorption and desorption ability for reaction substrates (reaction products), making high-entropy alloy catalysts widely studied in the catalytic field.

[0004] In recent years, researchers have synthesized a large number of high-entropy alloy materials and reported various synthesis methods, such as carbon thermal shock method, chemical vapor deposition method, microwave method and laser-assisted method, etc. Although researchers have conducted in-depth studies on the size, composition and morphology of high-entropy alloys, the metal content also plays a crucial role in the catalytic process. Therefore, it is particularly important to design and synthesize high-entropy alloy materials at the atomic scale and make their metal content flexibly adjustable.

[0005] Metal-organic frameworks have regular microstructures, and their organic linking ligands are easy to adjust and modify, providing possibilities for the design and synthesis of nanomaterials. In previous reports, when deriving high-entropy alloy materials from MOFs, metal ions serve as the connection points of MOF precursors. Due to the coordination saturation between metals and ligands, the content of metal ions cannot be changed, so high-entropy alloy materials with controllable metal loading cannot be obtained. However, the metal loading is an important indicator in supported catalysts, and different levels of active components may lead to different catalytic effects. Therefore, it is particularly important to flexibly adjust and precisely control the active metal composition. Summary of the Invention

[0006] In view of the disadvantages and deficiencies of the prior art, the present invention provides a controllable synthesis of high-entropy alloy composites. The high-entropy alloy composites are synthesized by weaving high-entropy metal-organic framework compounds (HEMOFs) with adjustable synthesis components based on a metal-ligand strategy, and using this as a precursor, thus solving the problem of non-adjustable metal components in the existing high-entropy alloy synthesis system.

[0007] To this end, according to the first aspect of the present invention, there is provided a high-entropy metal-organic framework compound, which is a reaction product of an organic ligand, a single-metal complex and a cerium source. Among them, the organic ligand includes 2,2'-bipyridine-5,5'-dicarboxylic acid, and the single-metal complex includes at least five of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex and Ir complex.

[0008] In some embodiments, the ligand L in the single-metal complex is 2,2'-bipyridine-5,5'-dicarboxylic acid.

[0009] In some embodiments, the single-metal complex includes five, six or seven of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex and Ir complex.

[0010] In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Rh complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ir complex. In some embodiments, the single-metal complex includes Pd complex, Ni complex, Cu complex, Rh complex and Ir complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex and Ir complex.

[0011] In some embodiments, the cerium source includes ammonium cerium nitrate.

[0012] According to a second aspect of the present invention, a method for preparing a high-entropy metal-organic framework compound is provided. The preparation method includes the following steps: reacting an organic ligand, a single-metal complex, and a cerium source to obtain the high-entropy metal-organic framework compound; wherein, the organic ligand includes 2,2'-bipyridine-5,5'-dicarboxylic acid, and the single-metal complex includes at least five of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex.

[0013] In some embodiments, the ligand L in the single-metal complex is 2,2'-bipyridine-5,5'-dicarboxylic acid.

[0014] In some embodiments, the single-metal complex includes five, six, or seven of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex.

[0015] In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Rh complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ir complex. In some embodiments, the single-metal complex includes Pd complex, Ni complex, Cu complex, Rh complex, and Ir complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex. In some embodiments, the single-metal complex includes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex.

[0016] In some embodiments, the cerium source includes ammonium cerium nitrate.

[0017] In some embodiments, the molar ratio of the single-metal complex to the organic ligand is 1:(0.5 - 10), preferably 1:(1 - 5), more preferably 1:1.5 - 2.5. In some specific embodiments, the molar ratio of the single-metal complex to the organic ligand is 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or any value therebetween.

[0018] In some embodiments, the molar ratio between the monometallic complexes is (0.5 - 1.5):(0.5 - 1.5), preferably 1:1. In some embodiments, the molar ratio between the monometallic complexes is 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5 or any value therebetween.

[0019] In some embodiments, the molar ratio of each monometallic complex to the organic ligand is 1:(5 - 25), preferably 1:8 - 12. In some specific embodiments, the molar ratio of each monometallic complex to the organic ligand is 1:5, 1:8, 1:10, 1:12, 1:15, 1:20, 1:25 or any value therebetween.

[0020] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex to the organic ligand is 1:1:1:1:1:5.

[0021] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex to the organic ligand is 1:1:1:1:1:10.

[0022] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex to the organic ligand is 1:1:1:1:1:15.

[0023] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex to the organic ligand is 1:1:1:1:1:20.

[0024] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ag complex to the organic ligand is 1:1:1:1:1:25.

[0025] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Rh complex to the organic ligand is 1:1:1:1:1:10.

[0026] In some specific embodiments, the molar ratio of the monometallic complexes Pt complex, Pd complex, Ni complex, Cu complex, Ir complex to the organic ligand is 1:1:1:1:1:10.

[0027] In some specific embodiments, the molar ratio of the monometallic complex (Pd complex, Ni complex, Cu complex, Rh complex, and Ir complex) to the organic ligand is 1:1:1:1:1:10.

[0028] In some specific embodiments, the molar ratio of the monometallic complex (Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex) to the organic ligand is 1:1:1:1:1:1:10.

[0029] In some specific embodiments, the molar ratio of the monometallic complex (Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex) to the organic ligand is 1:1:1:1:1:1:1:10.

[0030] In some embodiments, the molar ratio of the organic ligand to the cerium source is 1:(0.5 - 5), preferably 1:(1 - 2). In some embodiments, the molar ratio of the organic ligand to the cerium source is 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, or any value therebetween.

[0031] In some embodiments, the concentration of the organic ligand is 0.2 - 2 mM, preferably 0.5 - 1 mM. In some specific embodiments, the concentration of the organic ligand is 0.2 mM, 0.5 mM, 0.6 mM, 0.7 mM, 0.8 mM, 0.9 mM, 1 mM, 1.5 mM, 2 mM, or any value therebetween.

[0032] In some embodiments, the temperature of the reaction is 80 - 150 °C, preferably 90 - 110 °C. In some embodiments, the temperature of the reaction is 80 °C, 90 °C, 95 °C, 100 °C, 110 °C, 120 °C, 130 °C, 140 °C, 150 °C, or any value therebetween.

[0033] In some embodiments, the reaction time is 20 - 120 min, preferably 40 - 80 min. In some specific embodiments, the reaction time is 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, or any value therebetween.

[0034] In some embodiments, the method comprises the following steps:

[0035] S1: Mix the monometallic complex and the organic ligand in an organic solvent;

[0036] S2: React the cerium source with the mixed material obtained in step S1; and optionally

[0037] S3: Perform solid-liquid separation on the reaction product obtained in step S2, and wash and dry the obtained solid material.

[0038] In some embodiments, in step S1, the organic solvent includes N,N'-dimethylformamide.

[0039] In some embodiments, in step S1, the temperature of the mixing is 15 - 40 °C, for example, room temperature.

[0040] In some embodiments, in step S3, the washing is performed using dimethyl sulfoxide, N,N'-dimethylformamide, and / or acetone.

[0041] In some embodiments, in step S3, the drying temperature is 40 - 70 °C, for example, 40 min, 50 min, 60 min, 70 min, or any value therebetween.

[0042] According to a third aspect of the present invention, there is provided a high-entropy alloy composite material, which includes cerium dioxide and a carbon-supported high-entropy alloy, and the high-entropy alloy includes at least five of Pd, Pt, Ni, Cu, Ag, Rh, and Ir.

[0043] In some embodiments, the high-entropy alloy composite material is obtained by carbonizing and reducing the high-entropy metal-organic framework compound described in the first aspect of the present invention or the high-entropy metal-organic framework compound obtained by the preparation method described in the second aspect.

[0044] According to a fourth aspect of the present invention, there is provided a synthesis method of a high-entropy alloy composite material, and the synthesis method includes the following steps: calcine the high-entropy metal-organic framework compound described in the first aspect of the present invention or the high-entropy metal-organic framework compound obtained by the preparation method described in the second aspect in a reducing atmosphere to obtain the high-entropy alloy composite material.

[0045] In some embodiments, the calcination temperature is 600 - 1000 °C, preferably 700 - 850 °C. In some embodiments, the calcination temperature is 600 °C, 700 °C, 750 °C, 800 °C, 850 °C, 900 °C, 1000 °C, or any value therebetween.

[0046] In some embodiments, the calcination time is 0.5 - 6 h, preferably 1 - 3 h. In some embodiments, the calcination time is 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, or any value therebetween.

[0047] In some embodiments, the reducing atmosphere is a mixed gas of H2 / Ar.

[0048] In some embodiments, in the mixed gas, the volume content of H2 is 5-10%, such as 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween.

[0049] According to the fifth aspect of the present invention, there is provided an application of the high-entropy metal-organic framework compound described in the first aspect, or the high-entropy metal-organic framework compound obtained by the preparation method described in the second aspect, the high-entropy alloy composite material described in the third aspect, or the high-entropy alloy composite material obtained by the synthesis method described in the fourth aspect in catalysis, hydrogen storage, filtration, gas separation technology or electronic devices.

[0050] In some embodiments, the application is an application in a photocatalytic hydrogen production reaction.

[0051] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0052] (1) The present invention provides a high-entropy alloy composite material, which can be designed and synthesized into high-entropy alloy composite materials with different metal compositions and ratios, and exhibits excellent photocatalytic hydrogen production performance.

[0053] (2) In the synthesis method of the high-entropy alloy composite material of the present invention, a variety of metal ligands are used as linkers, and ammonium cerium nitrate is used as the cerium source of the metal node. A high-entropy metal-organic framework compound (HEMOFs) containing different metal combinations can be controllably synthesized, and the content and ratio of metals can be flexibly controlled. Different metal compositions and ratios of high-entropy alloy composite materials can be obtained by high-temperature reduction in a hydrogen-argon mixed gas. The high-entropy alloy composite materials with different metal combinations controllably synthesized by the present invention are widely applicable to various catalytic systems, expanding the application scope of high-entropy composite materials.

[0054] (3) In addition, the synthesis method of the present invention is simple and efficient, and is suitable for industrial production. Description of the Drawings

[0055] Figure 1 It is a structural diagram of a single-metal complex in some embodiments of the present invention, where a is LPd, b is LPt, c is LNi, d is LCu, e is LAg, f is LRh, and g is LIr.

[0056] Figure 2 It is an XRD pattern of the HEMOF2 material in some embodiments of the present invention.

[0057] Figure 3 It is a scanning electron micrograph of the HEMOF2 material in some embodiments of the present invention.

[0058] Figure 4 Transmission electron microscopy image of the HEMOF2 material in some embodiments of the present invention.

[0059] Figure 5 XRD pattern of the HEAs / CeO2 / C2 material in some embodiments of the present invention.

[0060] Figure 6 Scanning electron microscopy image of the HEAs / CeO2 / C2 material in some embodiments of the present invention.

[0061] Figure 7 Transmission electron microscopy image of the HEAs / CeO2 / C2 material in some embodiments of the present invention, where a is the low-magnification transmission electron microscopy image of HEAs / CeO2 / C2, b is the high-magnification atomic phase transmission electron microscopy image of HEAs particles, c is the Fourier transform pattern of b, and d is the elemental distribution map of Pt, Pd, Ni, Cu, and Ag elements in HEAs particles.

[0062] Figure 8 Synchrotron radiation characterization results of the HEAs / CeO2 / C2 material in some embodiments of the present invention.

[0063] Figure 9 Photocatalytic hydrogen production performance comparison chart of the HEAs(5L) / CeO2 / C, HEAs(10L) / CeO2 / C, HEAs(15L) / CeO2 / C, HEAs(20L) / CeO2 / C, and HEAs(25L) / CeO2 / C materials prepared in Examples 1-5 of the present invention.

[0064] Figure 10 Photocatalytic hydrogen production performance comparison chart of the HEAs(10L) / CeO2 / C prepared in Example 2 of the present invention and the Pt / CeO2 / C, Pd / CeO2 / C, Ni / CeO2 / C, Cu / CeO2 / C, and Ag / CeO2 / C prepared in Comparative Examples 1-5. Detailed implementation manners

[0065] The present invention proposes a new weaving strategy for synthesizing high-entropy alloys, enabling precise atomic-level control of metal components and contents. By using pre-synthesized single-metal ligand complexes (LMs) as "threads", the traditional challenges associated with the complex reaction kinetics during the formation of high-entropy metal-organic framework compounds (HEMOFs) are successfully overcome. Subsequently, these HEMOFs are transformed into CeO2 / C-supported HEAs, which exhibit excellent photocatalytic performance, achieving a hydrogen evolution rate exceeding that of traditional single-metal catalysts. This success highlights the potential of the weaving strategy to improve catalytic efficiency through uniform metal distribution and synergistic effects between multi-metal centers, laying a solid foundation for the future development of customized catalyst design and optimization, and making a significant contribution to clean energy applications.

[0066] To make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and do not constitute any limitation to the present invention. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessarily confusing the concepts of the present disclosure. Such structures and technologies have also been described in many publications.

[0067] The reagents and / or drugs used in the following embodiments are all commercially obtained or can be synthesized by known methods.

[0068] The following embodiments exemplarily describe a preparation method for controllably synthesizing high-entropy alloy composites based on a metal-ligand weaving strategy. The method includes: using 2,2'-bipyridine-5,5'-dicarboxylic acid (H2L) to synthesize seven examples of single-metal complexes based on Pt, Pd, Ni, Cu, Ag, Rh, and Ir (as shown in a-g in Figure 1 ), namely LPt, LPd, LNi, LCu, LNi, LAg, LRn, and LIr; using H2L, LPt, LPd, LNi, LCu, LNi, LAg, LRn, and LIr as linking ligands, adjusting the combinations and ratios of different metal ligands, and reacting with ammonium cerium nitrate respectively to successfully prepare high-entropy metal-organic framework compounds HEMOF1-HEMOF10. Finally, high-entropy alloy composites HEAs / CeO₂ / C1-HEAs / CeO₂ / C10 with different metal combinations and ratios are obtained by calcination reduction in a hydrogen-argon mixed atmosphere.

[0069] Among them, the single-metal complexes LPt, LPd, LNi, LCu, LNi, LAg, LRn, and LIr are prepared according to the following method:

[0070] Seven metal ligands, namely LPt, LPd, LNi, LCu, LAg, LRh, and LIr, were synthesized based on 2,2'-bipyridine-5,5'-dicarboxylic acid (H2L) and potassium tetrachloroplatinate, potassium tetrachloropalladate, nickel(II) chloride hexahydrate, copper(II) chloride dihydrate, silver nitrate, dichloro(pentamethylcyclopentadienyl)rhodium(III) dimer, and dichloro(pentamethylcyclopentadienyl)iridium(III) dimer, respectively.

[0071] Among them, the specific composition of HEMOF1 is as follows: Five metal ligands, LPt, LPd, LNi, LCu, and LAg, were combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:5 and reacted with ammonium cerium(IV) nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-5L.

[0072] Among them, the specific composition of HEMOF2 is as follows: Five metal ligands, LPt, LPd, LNi, LCu, and LAg, were combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:10 and reacted with ammonium cerium(IV) nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-10L.

[0073] Among them, the specific composition of HEMOF3 is as follows: Five metal ligands, LPt, LPd, LNi, LCu, and LAg, were combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:15 and reacted with ammonium cerium(IV) nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-15L.

[0074] Among them, the specific composition of HEMOF4 is as follows: Five metal ligands, LPt, LPd, LNi, LCu, and LAg, were combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:20 and reacted with ammonium cerium(IV) nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-20L.

[0075] Among them, the specific composition of HEMOF5 is as follows: Five metal ligands, LPt, LPd, LNi, LCu, and LAg, were combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:25 and reacted with ammonium cerium(IV) nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-25L.

[0076] Among them, the specific form of the HEMOF6 is as follows: Five metal ligands LPd, LPt, LNi, LCu, and LRh are selected and combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:10, and reacted with ammonium cerium nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPd-LPt-LNi-LCu-LRh-10L.

[0077] Among them, the specific form of the HEMOF7 is as follows: Five metal ligands LPd, LIr, LNi, LCu, and LRh are selected and combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:10, and reacted with ammonium cerium nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPd-LIr-LNi-LCu-LRh-10L.

[0078] Among them, the specific form of the HEMOF8 is as follows: Five metal ligands LPd, LIr, LNi, LCu, and LAg are selected and combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:10, and reacted with ammonium cerium nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPd-LIr-LNi-LCu-LAg-10L.

[0079] Among them, the specific form of the HEMOF9 is as follows: Six metal ligands LPd, LPt, LNi, LCu, LAg, and LRh are selected and combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:1:10, and reacted with ammonium cerium nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPd-LPt-LNi-LCu-LAg-LRh-10L.

[0080] Among them, the specific form of the HEMOF10 is as follows: Seven metal ligands LPd, LPt, LNi, LCu, LAg, LRh, and LIr are selected and combined with the organic ligand H2L in a molar mass ratio of 1:1:1:1:1:1:1:10, and reacted with ammonium cerium nitrate to obtain the high-entropy metal-organic framework compound UiO-67-Ce-LPd-LPt-LNi-LCu-LAg-LRh-LIr-10L.

[0081] Among them, the specific form of the HEAs / CeO2 / C1 is as follows: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-5L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain HEAs(5L) / CeO2 / C.

[0082] Among them, the specific form of the HEAs / CeO2 / C2 is as follows: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain HEAs(10L) / CeO2 / C.

[0083] Among them, the HEAs / CeO2 / C3 specifically is: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-15L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain HEAs(15L) / CeO2 / C.

[0084] Among them, the HEAs / CeO2 / C4 specifically is: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-20L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain HEAs(20L) / CeO2 / C.

[0085] Among them, the HEAs / CeO2 / C5 specifically is: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-25L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain HEAs(25L) / CeO2 / C.

[0086] Among them, the HEAs / CeO2 / C6 specifically is: UiO-67-Ce-LPd-LPt-LNi-LCu-LRh-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain PdPtNiCuRh / CeO2 / C.

[0087] Among them, the HEAs / CeO2 / C7 specifically is: UiO-67-Ce-LPd-LIr-LNi-LCu-LRh-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain PdIrNiCuRh / CeO2 / C.

[0088] Among them, the HEAs / CeO2 / C8 specifically is: UiO-67-Ce-LPd-LIr-LNi-LCu-LAg-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain PdIrNiCuAg / CeO2 / C.

[0089] Among them, the HEAs / CeO2 / C9 specifically is: UiO-67-Ce-LPd-LPt-LNi-LCu-LAg-LRh-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain PdPtNiCuAgRh / CeO2 / C.

[0090] Among them, the HEAs / CeO2 / C10 specifically is: UiO-67-Ce-LPt-LPd-LNi-LCu-LAg-LRh-LIr-10L is calcined and reduced in a hydrogen-argon mixed atmosphere to obtain PdPtNiCuAgRhIr / CeO2 / C.

[0091] Among them, the method specifically includes the following steps:

[0092] Step 1, Synthesize seven metal ligands LPt, LPd, LNi, LCu, LNi, LAg, LRh and LIr based on 2,2'-bipyridine-5,5'-dicarboxylic acid (H2L) and potassium tetrachloroplatinate, potassium tetrachloropalladate, nickel(II) chloride hexahydrate, copper(II) chloride dihydrate, silver nitrate, dichloro(pentamethylcyclopentadienyl)rhodium dimer and dichloro(pentamethylcyclopentadienyl)iridium dimer respectively;

[0093] Step 2, Add H2L, LPt, LPd, LNi, LCu, LNi, LAg, LRh and LIr (a total of 1.065 mmol) into a 50 mL round-bottom flask in different proportions and combinations. After adding N,N-dimethylformamide (DMF; 6.0 mL), add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the round-bottom flask as well. Seal the round-bottom flask and stir and heat it at 100 °C for 1.0 h. After the reaction is completed, cool it to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, wash the obtained solid with acetone (10.0 mL) again, and then centrifuge it twice. Then dry the obtained solid powder in a vacuum drying oven at 50 °C and collect it for standby.

[0094] Step 3, Prepare HEAs / CeO2 / C1-HEAs / CeO2 / C10 materials using HEMOF1-HEMOF10 as precursors. Specifically, calcine the HEMOF1-HEMOF10 materials in a tubular furnace under a mixed gas atmosphere of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature to obtain black powder, which is collected to obtain HEAs / CeO2 / C1-HEAs / CeO2 / C10 materials.

[0095] Specifically as follows:

[0096] Example 1

[0097] Step 1, Weigh 0.533 mmol of H2L, 0.107 mmol of LPt, 0.107 mmol of LPd, 0.107 mmol of LNi, 0.107 mmol of LCu and 0.107 mmol of LAg into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make it mix evenly.

[0098] Step 2, Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above-mentioned round-bottom flask as well, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0099] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF1 is collected.

[0100] Step 4: HEMOF1 is placed in a corundum boat and calcined in a tube furnace under an atmosphere of a mixed gas of H2 / Ar (8% H2). It is heated to 800 °C at a heating rate of 5 °C·min -1 and heated for 2 h, and then naturally cooled to room temperature. The black powder is collected to obtain the HEAs / CeO2 / C1 material.

[0101] Example 2

[0102] Step 1: Weigh 0.71 mmol of H2L, 0.071 mmol of LPt, 0.071 mmol of LPd, 0.071 mmol of LNi, 0.071 mmol of LCu and 0.071 mmol of LAg into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make it mix evenly.

[0103] Step 2: An aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) is also added to the above round-bottom flask. The round-bottom flask is sealed and stirred and heated at 100 °C for 1.0 h.

[0104] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF2 is collected.

[0105] Step 4: HEMOF2 is placed in a corundum boat and calcined in a tube furnace under an atmosphere of a mixed gas of H2 / Ar (8% H2). It is heated to 800 °C at a heating rate of 5 °C·min -1 and heated for 2 h, and then naturally cooled to room temperature. The black powder is collected to obtain the HEAs(10L) / CeO2 / C2 material.

[0106] The successful synthesis of HEMOF2 was confirmed by powder X-ray diffraction (PXRD) analysis (as Figure 2As shown). Scanning electron microscope (SEM) images show that the HEMOF2 material is a bulk structure composed of aggregated small particles (as Figure 3 shown). In addition, energy-dispersive X-ray spectroscopy (EDS) maps indicate that different metal elements are uniformly distributed within the MOF framework (as Figure 4 shown). By carbonizing the HEMOF2 precursor, HEAs(10L) / CeO2 / C was synthesized. The PXRD pattern not only shows diffraction peaks belonging to CeO2, where the peaks at 2θ = 28.5° and 47.6° are assigned to the (111) and (220) crystal planes of CeO2, but also the peaks at 2θ = 40°, 46.6° and 68.1° correspond to the (111), (200) and (220) crystal planes of HEA, respectively (as Figure 5 shown). Compared with MOF (HEMOF2), the morphology of HEA(10L) / CeO2 / C shows no obvious change (as Figure 6 shown). Further characterization of HEAs(10L) / CeO2 / C by high-angle annular dark-field transmission electron microscopy (HAADF-STEM) provides conclusive evidence for the successful preparation of high-entropy alloy nanoparticles (HEAs NP) on the CeO2 / C composite support (as Figure 7 a shown). The lattice spacings of 0.178 nm and 0.204 nm are clearly distinguishable, corresponding to the (111) and (200) planes of the face-centered cubic (FCC) phase of HEAs NP, respectively (as Figure 7 b shown). These lattice fringes are in good agreement with the PXRD crystal plane results through Fourier transform (FFT) analysis (as Figure 7 c shown). As Figure 7 d shown, the elemental distribution map shows that Pt, Pd, Ni, Cu and Ag elements are uniformly distributed in the HEA NP. The successful preparation of HEAs was demonstrated by synchrotron radiation characterization technology (as Figure 8 shown).

[0107] Comparative Example 1

[0108] Step 1: Weigh 0.71 mmol of H2L and 0.355 mmol of LPt in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0109] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat at 100 °C for 1.0 h.

[0110] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and UiO-67-Ce-5LPt is collected.

[0111] Step 4: Put UiO-67-Ce-5LPt into a corundum boat and calcine it in a tube furnace under a mixed gas atmosphere of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. The black powder is collected to obtain the Pt / CeO2 / C material.

[0112] Comparative Example 2

[0113] Step 1: Weigh 0.71 mmol of H2L and 0.355 mmol of LPd in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix evenly.

[0114] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat at 100 °C for 1.0 h.

[0115] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and UiO-67-Ce-5LPd is collected.

[0116] Step 4: Put UiO-67-Ce-5LPd into a corundum boat and calcine it in a tube furnace under a mixed gas atmosphere of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. The black powder is collected to obtain the Pd / CeO2 / C material.

[0117] Comparative Example 3

[0118] Step 1: Weigh 0.71 mmol of H2L and 0.355 mmol of LNi in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix evenly.

[0119] Step 2: Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat at 100 °C for 1.0 h.

[0120] Step 3: After the reaction is completed, cool to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and UiO-67-Ce-5LNi is collected.

[0121] Step 4: Place UiO-67-Ce-5LNi in a corundum boat and calcine it in a tubular furnace under a mixed gas atmosphere of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. Collect the obtained black powder to obtain the Ni / CeO2 / C material.

[0122] Comparative Example 4

[0123] Step 1: Weigh 0.71 mmol of H2L and 0.355 mmol of LCu in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0124] Step 2: Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat at 100 °C for 1.0 h.

[0125] Step 3: After the reaction is completed, cool to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and UiO-67-Ce-5LCu is collected.

[0126] Step 4: Place UiO-67-Ce-5LCu in a corundum boat and calcine it in a tubular furnace under a mixed gas atmosphere of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. Collect the obtained black powder to obtain the Cu / CeO2 / C material.

[0127] Comparative Example 5

[0128] Step 1: Weigh 0.71 mmol of H2L and 0.355 mmol of LAg in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0129] Step 2: Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above-mentioned round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0130] Step 3: After the reaction is completed, cool it to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and UiO-67-Ce-5LAg is collected.

[0131] Step 4: Put UiO-67-Ce-5LAg into a corundum boat and calcine it in a tube furnace under an atmosphere of a mixed gas of H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. Collect the obtained black powder to obtain the Ag / CeO2 / C material.

[0132] Example 3

[0133] Step 1: Weigh 0.799 mmol of H2L, 0.053 mmol of LPt, 0.053 mmol of LPd, 0.053 mmol of LNi, 0.053 mmol of LCu and 0.053 mmol of LAg in a 50 mL flask, then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0134] Step 2: Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above-mentioned round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0135] Step 3: After the reaction is completed, cool it to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF3 is collected.

[0136] Step 4, Put HEMOF3 into a corundum boat and calcine it in a tube furnace under an atmosphere of mixed gas H2 / Ar (8% H2). Heat it to 800 °C at a heating rate of 5 °C·min -1 and keep heating for 2 h, then let it cool down to room temperature naturally. Collect the obtained black powder to get the HEAs / CeO2 / C3 material.

[0137] Example 4

[0138] Step 1, Weigh 0.852 mmol of H2L, 0.043 mmol of LPt, 0.043 mmol of LPd, 0.043 mmol of LNi, 0.043 mmol of LCu and 0.043 mmol of LAg into a 50 mL flask. Then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0139] Step 2, Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0140] Step 3, After the reaction, let it cool down to room temperature. Separate the pale yellow precipitate from the mother liquor by centrifugation and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, wash the obtained solid with acetone (10.0 mL) and then centrifuge it twice. Then dry the obtained solid powder in a vacuum drying oven at 50 °C and collect it to get HEMOF4.

[0141] Step 4, Put HEMOF4 into a corundum boat and calcine it in a tube furnace under an atmosphere of mixed gas H2 / Ar (8% H2). Heat it to 800 °C at a heating rate of 5 °C·min -1 and keep heating for 2 h, then let it cool down to room temperature naturally. Collect the obtained black powder to get the HEAs / CeO2 / C4 material.

[0142] Example 5

[0143] Step 1, Weigh 0.888 mmol of H2L, 0.036 mmol of LPt, 0.036 mmol of LPd, 0.036 mmol of LNi, 0.036 mmol of LCu and 0.036 mmol of LAg into a 50 mL flask. Then add 6.0 mL of N,N'-dimethylformamide (DMF) and mix them evenly.

[0144] Step 2, Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0145] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF5 is collected.

[0146] Step 4: Put HEMOF5 into a corundum boat and calcine it in a tube furnace under the atmosphere of a mixed gas of H2 / Ar (8% H2). Heat it to 800 °C at a heating rate of 5 °C·min -1 and keep heating for 2 h, then let it cool down to room temperature naturally. The black powder is collected to obtain the HEAs / CeO2 / C5 material.

[0147] Example 6

[0148] Step 1: Weigh 0.71 mmol of H2L, 0.071 mmol of LPd, 0.071 mmol of LPt, 0.071 mmol of LNi, 0.071 mmol of LCu and 0.071 mmol of LRh into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make them mix evenly.

[0149] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0150] Step 3: After the reaction is completed, the temperature is lowered to room temperature. The pale yellow precipitate is separated from the mother liquor by centrifugation and washed twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF6 is collected.

[0151] Step 4: Put HEMOF6 into a corundum boat and calcine it in a tube furnace under the atmosphere of a mixed gas of H2 / Ar (8% H2). Heat it to 800 °C at a heating rate of 5 °C·min -1 and keep heating for 2 h, then let it cool down to room temperature naturally. The black powder is collected to obtain the HEAs / CeO2 / C6 material.

[0152] Example 7

[0153] Step 1: Weigh 0.71 mmol of H2L, 0.071 mmol of LPd, 0.071 mmol of LIr, 0.071 mmol of LNi, 0.071 mmol of LCu and 0.071 mmol of LRh into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make it mix evenly.

[0154] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0155] Step 3: After the reaction is completed, cool it to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF7 is collected.

[0156] Step 4: Put HEMOF7 into a corundum boat and calcine it in a tube furnace under a mixed gas atmosphere of H2 / Ar (8% H2), with a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. Collect the black powder to obtain the HEAs / CeO2 / C7 material.

[0157] Example 8

[0158] Step 1: Weigh 0.71 mmol of H2L, 0.071 mmol of LPd, 0.071 mmol of LPt, 0.071 mmol of LNi, 0.071 mmol of LCu and 0.071 mmol of LIr into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make it mix evenly.

[0159] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0160] Step 3: After the reaction is completed, cool it to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF8 is collected.

[0161] Step 4: Place HEMOF8 into a corundum boat and calcine it in a tubular furnace under an atmosphere of mixed gas H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and then naturally cool to room temperature to obtain a black powder, which is collected to obtain the HEAs / CeO2 / C8 material.

[0162] Example 9

[0163] Step 1: Weigh 0.666 mmol of H2L, 0.067 mmol of LPt, 0.067 mmol of LPd, 0.067 mmol of LNi, 0.067 mmol of LCu, 0.067 mmol of LAg, and 0.067 mmol of LRh into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make them mix evenly.

[0164] Step 2: Add an aqueous solution of ammonium cerium nitrate (2.0 mL, 2.665 M) to the above round-bottom flask, seal the round-bottom flask, and stir and heat at 100 °C for 1.0 h.

[0165] Step 3: After the reaction is completed, cool to room temperature, separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C and collected to obtain HEMOF9.

[0166] Step 4: Place HEMOF9 into a corundum boat and calcine it in a tubular furnace under an atmosphere of mixed gas H2 / Ar (8% H2) at a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and then naturally cool to room temperature to obtain a black powder, which is collected to obtain the HEAs / CeO2 / C9 material.

[0167] Example 10

[0168] Step 1: Weigh 0.626 mmol of H2L, 0.063 mmol of LPt, 0.063 mmol of LPd, 0.063 mmol of LNi, 0.063 mmol of LCu, 0.063 mmol of LAg, 0.063 mmol of LRh, and 0.063 mmol of LIr into a 50 mL flask, and then add 6.0 mL of N,N'-dimethylformamide (DMF) to make them mix evenly.

[0169] Step 2: Add an aqueous solution of ammonium cerium(IV) nitrate (2.0 mL, 2.665 M) to the above-mentioned round-bottom flask, seal the round-bottom flask, and stir and heat it at 100 °C for 1.0 h.

[0170] Step 3: After the reaction is completed, cool it to room temperature. Separate the pale yellow precipitate from the mother liquor by centrifugation, and wash it twice with dimethyl sulfoxide (DMSO; 10.0 mL) and DMF (10.0 mL). To remove DMF from the product, the obtained solid is washed with acetone (10.0 mL) and then centrifuged twice. Then the obtained solid powder is dried in a vacuum drying oven at 50 °C, and HEMOF10 is collected.

[0171] Step 4: Put HEMOF10 into a corundum boat and calcine it in a tube furnace under an atmosphere of mixed gas H2 / Ar (8% H2), with a heating rate of 5 °C·min -1 to 800 °C, heat for 2 h, and naturally cool to room temperature. Collect the obtained black powder to obtain the HEAs / CeO2 / C10 material.

[0172] Application Example

[0173] The photocatalytic hydrogen production performance of HEAs(5L) / CeO2 / C, HEAs(10L) / CeO2 / C, HEAs(15L) / CeO2 / C, HEAs(20L) / CeO2 / C, and HEAs(25L) / CeO2 / C prepared in Examples 1-5 was tested. The test method is as follows:

[0174] Carry out photocatalytic reduction of water in a Labsolar-6A system (Beijing Perfectlight Technology Co., Ltd.). Use a xenon lamp (Beijing Perfectlight Technology Co., Ltd.) with 300 W as the light source. Add 10.0 mg of photocatalyst powder and 20.0 mg of eosin (EY) to a mixed solution containing 3.0 mL of triethanolamine and 27.0 mL of water in a 200 mL quartz reaction cell. During the reaction, analyze the gas products with a gas chromatograph (GC9790 II) equipped with a thermal conductivity detector and a flame ionization detector. Control the temperature of the reaction system at 25 °C through a circulating cooling water system.

[0175] The test results are as Figure 9 shown. The results show that when the molar ratio of each metal ligand to the organic ligand is 1:10, the HEAs(10L) / CeO2 / C material derived from HEMOF2 exhibits excellent photocatalytic hydrogen production performance, and the H2 evolution rate is 13.4 mmol·g -1 ·h -1 .

[0176] The photocatalytic hydrogen production performance of the HEAs(10L) / CeO2 / C prepared in Example 2 was tested against Pt / CeO2 / C, Pd / CeO2 / C, Ni / CeO2 / C, Cu / CeO2 / C, and Ag / CeO2 / C prepared in Comparative Examples 1-5.

[0177] The test results are as Figure 10 shown, and the results indicate that the cerium oxide-supported high-entropy alloy material exhibits excellent photocatalytic hydrogen production performance compared to single-metal nanoparticles supported on cerium oxide.

[0178] As can be seen from the above examples, the method of the present invention combines the pre-synthesis of metal-ligand complexes (LM) to address the complex reaction kinetics typically associated with various metal nodes and ligands. Through careful design and synthesis, and precise adjustment of their dosage and ratio, high-entropy metal-organic framework compounds (HEMOF) with different metal compositions were successfully constructed, using cerium oxide clusters as metal nodes. After carbonization and reduction, these HEMOF were transformed into HEAs supported by the co-catalyst CeO2 / C, which have adjustable metal content and variable catalytic activity. The evaluation of photocatalytic water splitting performance shows that the high-entropy alloy composite materials of the present invention exhibit excellent catalytic activity and high H2 evolution rates. This breakthrough method can not only regulate the metal content in high-entropy composite materials at the atomic level, but also significantly expand the range of applicable metal ions, enhance their uniform distribution, thus promoting the systematic design and development of efficient catalysts.

[0179] The technical solution of the present invention is not limited to the limitations of the above specific embodiments. Any technical deformation made according to the technical solution of the present invention falls within the protection scope of the present invention.

Claims

1. A high-entropy metal-organic framework compound, comprising a reaction product of an organic ligand, a single-metal complex and a cerium source, wherein, The organic ligand includes 2,2'-bipyridine-5,5'-dicarboxylic acid, and the single-metal complex includes at least five of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex.

2. The high-entropy metal-organic framework compound according to claim 1, wherein The ligand L in the single-metal complex is 2,2'-bipyridine-5,5'-dicarboxylic acid; and / or The single-metal complex includes five, six, or seven of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex; and / or The cerium source includes ammonium cerium nitrate.

3. A preparation method of a high-entropy metal-organic framework compound, comprising the following steps: Reacting the organic ligand, the single-metal complex, and the cerium source to obtain the high-entropy metal-organic framework compound; wherein the organic ligand includes 2,2'-bipyridine-5,5'-dicarboxylic acid, and the single-metal complex includes at least five of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex.

4. The preparation method according to claim 3, characterized in that, The ligand L in the single-metal complex is 2,2'-bipyridine-5,5'-dicarboxylic acid; and / or The single-metal complex includes at least five of Pt complex, Pd complex, Ni complex, Cu complex, Ag complex, Rh complex, and Ir complex; and / or The cerium source includes ammonium cerium nitrate.

5. The preparation method according to claim 3 or 4, characterized in that, The molar ratio of the single-metal complex to the organic ligand is 1:(0.5 - 10), preferably 1:(1 - 5); and / or The molar ratio between any two of the single-metal complexes is (0.5 - 1.5):(0.5 - 1.5), preferably 1:1; and / or The molar ratio of each single-metal complex to the organic ligand is 1:(5 - 25), preferably 1:(8 - 12); and / or The molar ratio of the organic ligand to the cerium source is 1:(0.5 - 5), preferably 1:(1 - 2); and / or The concentration of the organic ligand is 0.2 - 2 mM, preferably 0.5 - 1 mM; and / or The temperature of the reaction is 80 - 150 °C, preferably 90 - 110 °C; and / or The time of the reaction is 20 - 120 min, preferably 40 - 80 min.

6. The preparation method according to any one of claims 3-5, characterized in that, The method includes the following steps: S1: Mixing the single-metal complex and the organic ligand in an organic solvent; S2: Reacting the cerium source with the mixed material obtained in step S1; and optionally S3: Separating the solid-liquid of the reaction product obtained in step S2, and washing and drying the obtained solid material; Preferably, in step S1, the organic solvent includes N,N'-dimethylformamide; Preferably, in step S3, the washing is carried out with dimethyl sulfoxide, N,N'-dimethylformamide, and / or acetone; Preferably, in step S3, the drying temperature is 40 - 70 °C.

7. A high-entropy alloy composite material, comprising cerium dioxide and a carbon-supported high-entropy alloy, and the high-entropy alloy includes at least five of Pd, Pt, Ni, Cu, Ag, Rh, and Ir; Preferably, the high-entropy alloy composite material is obtained by carbonization and reduction of the high-entropy metal-organic framework compound described in claim 1 or 2 or the high-entropy metal-organic framework compound obtained by the preparation method described in any one of claims 3-6.

8. A method for synthesizing a high-entropy alloy composite material, comprising the following steps: Calcining the high-entropy metal-organic framework compound described in claim 1 or 2 or the high-entropy metal-organic framework compound obtained by the preparation method described in any one of claims 3-6 in a reducing atmosphere to obtain the high-entropy alloy composite material.

9. The synthesis method according to claim 8, characterized in that, The temperature of the calcination is 600-1000 °C, preferably 700-850 °C; and / or The time of the calcination is 0.5-6 h, preferably 1-3 h; and / or The reducing atmosphere is a mixed gas of H2 / Ar. Preferably, in the mixed gas, the volume content of H2 is 5-10%.

10. Application of the high-entropy metal-organic framework compound described in claim 1 or 2 or the high-entropy metal-organic framework compound obtained by the preparation method described in any one of claims 3-6, the high-entropy alloy composite material described in claim 7, or the high-entropy alloy composite material obtained by the synthesis method described in claim 8 or 9 in catalysis, hydrogen storage, filtration, gas separation technology or electronic devices, preferably in photocatalytic hydrogen production reaction.

Citation Information

Cited By

  • Preparation method and application of nano high-entropy metal organic framework material

    CN122325769A